Coupling structural and functional thresholds for vegetation changes on a Mongolian shrubland. (October 2018) - Sasaki, Takehiro; Koyama, Asuka; Okuro, Toshiya
Highlights: Shrub cover exhibited a threshold response along a grazing gradient. Wind erosion accelerated when shrub cover reached a threshold value of 5.3%. The management recommendation is to maintain the shrub cover well above 7%. Abstract: The concept of an ecological threshold has spurred important advances in understanding the nonlinear responses of ecosystems to various disturbances. Yet integrated evaluations of an ecosystem's structural threshold and functional threshold are rare, and we know little about linkages between observed nonlinear changes in ecosystem structure along disturbance gradients and the associated changes in system feedbacks. We applied a two-step approach to perform integrated evaluations of structural and functional thresholds in a Mongolian shrubland. First, by using 6 years of data from plant communities along a gradient of grazing intensity, we identified the structural threshold in the changes in shrub cover along the gradient. We then identified the functional threshold at which wind erosion rates were accelerated due to sufficient decline in shrub cover. We found that shrub cover changed abruptly along the grazing gradient, indicating the presence of a structural threshold. Shrub cover decreased gradually along the grazing gradient to the threshold of 6.9%; thereafter it decreased rapidly. This level of shrub cover was close to that of the functional threshold (5.3%), namely the point at which the rate of wind erosion was accelerated. Our key finding is the coupling of structural and functional thresholds, suggesting that the modification of feedbacks between wind erosion and shrub cover might be associated with the nonlinear response of ecosystem structure to grazing. To bridge the gap between management applications and ecological threshold theory, it is essential to understand the potential feedback mechanisms that would contribute to nonlinear changes in ecosystem structure.